Prevalence, distribution, enterotoxin profiles, antimicrobial resistance, and genetic diversity of Bacillus cereus group isolates from lettuce farms in Korea - Rajalingam, Nagendran; Jung, Jieun; Seo, Seung-Mi; Jin, Hyun-Sook; Kim, Bo-Eun; Jeong, Myeong-In; Kim, Dawoon; Ryu, Jae-Gee; Ryu, Kyoung-Yul; Oh, Kwang Kyo (Frontiers in Microbiology, 2022)
Lettuce wraps are most popular in Korean cuisine for their high nutritional value and versatility in including them in multiple dishes. Microbial contamination of lettuce is a major concern as they are consumed fresh without cooking. Among other foodborne pathogens, the spore-forming, facultative anaerobic bacterium, Bacillus cereus is the most frequently detected pathogen in lettuce. In this study, we investigated the prevalence and distribution of Bacillus cereus strains in lettuce production farms and further evaluated the enterotoxin gene profiles, antibiotic susceptibility, multidrug resistance pattern and genetic differences among the Bacillus cereus group isolates. Of the 140 samples isolated from ten lettuce production farms, 21.42% of samples were positive for B. cereus in which 30.6% and 23.25% were from soil and lettuce respectively. The enterotoxin patterns A (hblCDA, nheABC, entFM, and cytK gene) and B (hblCDA, nheABC and entFM gene) accounted for 50% and 20% of all the isolates whereas the emetic gene ces was not detected in any of the B. cereus group isolates. Antibiotic susceptibility testing of the Bacillus cereus group isolates revealed that all the strains were predominantly resistant to β-lactam antibiotics except impenem and generally susceptible to most of the non β-lactam antibiotics including gentamycin, streptomycin, chloramphenicol and tetracycline. ERIC-PCR and MLST analysis revealed high genetic diversity among the 30 Bacillus cereus group isolates which belonged to 26 different sequence types (STs) and 7 new (STs). Moreover, the results of MLST coincided with the patterns of antibiotic resistance and enterotoxin profiles of the isolates. The result of this study indicates the higher prevalence of Bacillus cereus group isolates in lettuce production farms at the Republic of Korea.